Identification of Hymenolepis diminuta Cysticercoid Larvae in Tribolium castaneum (Coleoptera:Tenebrionidae) Beetles from Iran - Gholamreza Mowlavi; Farideh Shahbazi; Mohammad Reza Abai; Faezeh Najafi; Bibi Razieh Hosseini-Farash; Salma Teimoori; Hamid Hasanpour; Saied Reza Naddaf (Tehran University of Medical Sciences, 2017)
Background: Hymenolepis diminuta is a cestod of rodents and rarely infects humans. Infection in humans is via ingestion of infected insects. This study was aimed to detect H. diminuta cysticercoids in red flour beetles, Tribolium castaneum, and cockroaches originated from different regions of Iran. Methods: The red flour beetles and cockroaches were collected from local bakeries in five cities including Tehran, Ahvaz, Kazerun, and Sabzevar during 2010-2011. Some beetles and cockroaches were colonized in insectary and adults from F1 generation were fed on H. diminuta eggs. Both laboratory-infected and field-collected samples were dissected and examined for cysticercoids. Detection of H. diminuta DNA in T. castaneum beetles was performed by targeting a partial sequence of Ribosomal gene. Results: Except the beetles from Ahvaz, all specimens were negative for cysticercoid by microscopy. Of the four dissected beetles from Ahvaz, one harbored 12 cysticercoids. Also, 110 (52%) of laboratory-infected beetles showed infection with an average of 12-14 larvae. None of the cockroaches was infected. Two beetles from Ahvaz, including the remainder of the microscopic positive specimen, yielded the expected amplicon in PCR assay. The H. diminuta DNA sequences generated in this study were identical and matched 97-100% with similar sequences from GenBank database. Conclusion: Lack of infection in the majority of beetles may reflect a low rat infestation rate in those areas, alternatively, the examined specimens might not have been the representative samples of the T. castaneum populations.